When are employees idea champions? When they achieve progress at, find meaning in, and identify with work - De Clercq, D.; Pereira, R. (Personnel Review, 2021)
Purpose: Drawing from conservation of resources (COR) theory, this study investigates the relationship between employees' perceived career progress and their championing behavior and particularly how this relationship might be invigorated by two critical personal resources at the job (work meaningfulness) and employer (organizational identification) levels. Design/methodology/approach: Quantitative data were collected from a survey administered to 245 employees in an organization that operates in the oil industry. Findings: Beliefs about organizational support for career development are more likely to stimulate idea championing when employees find their job activities meaningful and strongly identify with the successes and failures of their employing organization. Practical implications: This study offers organizations deeper insights into the personal circumstances in which positive career-related energy is more likely to be directed toward the active mobilization of support for novel ideas. Originality/value: As a contribution to extant championing research, this research details how employees' perceived career progress spurs their relentless efforts to push novel ideas, based on their access to complementary personal resources.